2006
DOI: 10.1385/endo:29:2:243
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Neurological Disease: Role of Estrogens and Cytokines

Abstract: Increasing evidence suggests that inflammatory response may be a critical component of different brain pathologies. However, the role played by this reaction is not fully understood. The present findings suggest that neuroinflammtory mediators such as cytokines may be involved in a number of key steps in the pathological cascade of events leading to neuronal injury. This hypothesis is strongly supported by experimental and clinical observations indicating that inhibition of the inflammatory reaction correlates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 173 publications
2
80
0
Order By: Relevance
“…Our study revealed that the frequency of stroke in children is also more common in males than females (53.3% versus 46.7%). The same trend has been clarified in other worldwide childhood stroke studies (10), inspite of absence of estrogen predominance before puberty (11). Severity of stroke in most of our children (91.7%) measured by pediatric NIHSS was mild and mild to moderate with lateralization as the most common presenting complaint in (73.3%) of patients.…”
Section: Results:-supporting
confidence: 86%
“…Our study revealed that the frequency of stroke in children is also more common in males than females (53.3% versus 46.7%). The same trend has been clarified in other worldwide childhood stroke studies (10), inspite of absence of estrogen predominance before puberty (11). Severity of stroke in most of our children (91.7%) measured by pediatric NIHSS was mild and mild to moderate with lateralization as the most common presenting complaint in (73.3%) of patients.…”
Section: Results:-supporting
confidence: 86%
“…Additionally, estrogen has been shown to regulate GSK-3 activity in the hippocampus (58). This sex hormone-dependent regulation of GSK-3 signalling might explain why there are gender differences in regards to AD and why estrogen could be neuroprotective (59). This issue has not been addressed yet, even though it is clear that there are substantial sex differences in the mechanisms underlying memory formation (60)(61)(62).…”
Section: Discussionmentioning
confidence: 99%
“…The overall male predominance in adult stroke has been attributed to neuroprotective effects of estrogen. 22 It is possible that endocrine factors play a role in pediatric stroke. However, we found no difference in the gender ratio between preadolescent compared with adolescent children, making it more difficult to ascribe this gender difference to sex hormones.…”
Section: Golomb Et Al Male Predominance In Childhood Ischemic Strokementioning
confidence: 99%